Macrolide resistance due to erm(55) - David C. Alexander; Tayah Farquhar; Joshua M. E. Adams; Danae M. Suchan; Sean D. Workman; Richard J. Wallace Jr.; Barbara A. Brown-Elliott; Omar M. El-Halfawy; Andrew D. S. Cameron (Microbiology Spectrum, 2025)
ABSTRACT Antimicrobial resistance (AMR) is a global threat. The identification and characterization of novel resistance genes is integral to AMR surveillance. The erm(55) gene was originally identified through whole genome sequencing of macrolide-resistant strains of Mycobacterium chelonae. The gene was annotated as a ribosomal methyltransferase, but its role as a determinant of macrolide resistance was not formally demonstrated. Three erm(55) alleles have now been documented. The plasmid-borne erm(55)P, the transposon-associated erm(55)T, and the chromosomal encoded erm(55)C exhibit ≈82% amino acid sequence identity. Here, we confirm that, when expressed from plasmids in a macrolide-susceptible strain of Escherichia coli, all three erm(55) variants confer resistance to azithromycin and clarithromycin.IMPORTANCEMacrolide antibiotics are often the only oral treatment option for infections with rapidly growing mycobacteria such as Mycobacterium abscessus and Mycobacterium chelonae. We previously identified three variants of a newly predicted macrolide resistance gene, erm(55), in M. chelonae, including the first case of a plasmid-mediated macrolide resistance in mycobacteria. The present study provides experimental evidence that the three erm(55) variants confer macrolide resistance and that each variant is unique in the degree to which it reduces susceptibility to clinically relevant macrolides.